Determinisme Teknologi: Penggunaan ICT dalam Pembelajaran Daring - Clarissa Adeline; Irwansyah Irwansyah (Universitas Merdeka Malang, 2022)
This study aims to see how technology has determined our learning system through the use of ICT in online learning. The use of technology in the education sector brings a massive transformation in our learning system. In addition to that, the emergence of Covid 19 has also changed the education system into online learning. This study uses a qualitative approach and systematic literature review approach. Data collection used are observation and semi-structured interview with 2 informants that actively involved in online learning. The validity of this research use source triangulation. The result of this study shows that the ICT is used in every stages of learning process, from preparation, delivery and evaluation stage. Online learning cannot be separated from the role of technology, and it is shown that technology has determined online learning process. Keywords: Technology Determinism, ICT, Online Learning